Cellular automata and many-particle systems modeling aggregation behavior among populations - Morale, Daniela (Zielona Góra: Uniwersytet Zielonogórski)
A cellular automaton model is presented in order to describe mutual interactions among the individuals of a population due to social decisions. The scheme is used for getting qualitative results, comparable to field experiments carried out on a population of ants which present an aggregative behavior. We also present a second description of a biological spatially structured population of N individuals by a system of stochastic differential equations of Itô type. A "law of large numbers" to a continuum dynamics described by an integro-differential equation is given.
Keywords: cellular automata; individual-based models; stochastic differential equations; law of large numbers; density-dependence; nonlinear integrodifferential equations